Aspek Sumber Daya Manusia dan Ruang Terbuka Olahraga Ditinjau Dari Sport Development Index Di Kabupaten Banyumas Tahun 2022 (Indonesian Journal for Physical Education and Sport, 2022)
The background of this research is to examine human resources and the availability of open space to be reviewed from the sports development index in Banyumas Regency. The purpose of this study was to determine the sports development index in the aspect of human resources and sports open space in the field of sports in Banyumas Regency in terms of the sports development index. This type of research is descriptive quantitative with survey techniques. The target of this research is in 3 sub-districts, namely Somagede District. Banyumas, and Sokaraja in Banyumas Regency. The results of this study are the human resource index of 0.00057 and the sports open space index of 0.56. The conclusion of this study is that the human resource index in Banyumas Regency is in the low category and the sports open space index in Banyumas Regency is in the medium category.